Accuracy Measures and Fourier Analysis for the Full Multigrid Algorithm - Rodrigo, Carmen; Gaspar, Francisco J.; Oosterlee, Cornelis W.; Yavneh, Irad (SIAM journal on scientific computing, 2010)
The full multigrid (FMG) algorithm is often claimed to achieve so-called discretization-level accuracy. In this paper, this notion is formalized by defining a worst-case relative accuracy measure, denoted ..., which compares the total error of the ...-level FMG solution against the inherent discretization error. This measure can be used for tuning algorithmic compoents so as to obtain discretization-level accuracy. A Fourier analysis is developed for estimating ..., and the resulting estimates are confirmed by numerical tests. (ProQuest: ... denotes formulae/symbols omitted.)